Determine Timeliness Submission of Financial Statements of Manufacturing Companies in Indonesia Stock Exchange - Nurhasanah Nurhasanah; Husaini Husaini; Nur Ilmi Febriani (Faculty of Economics and Business, Universitas Malikussaleh, 2021)
This study aims to analyze the effect of Firm Age, Profitability andLeverage on the timeliness of submitting financial reports in manufacturingcompanies on the Indonesia Stock Exchange. The populations aremanufacturing companies that have gone public listed on the Indonesia StockExchange (IDX) during the 2019-2020, which are 182 companies. Obtainedsampling used purposive sampling method. Based on this method the sampleobtained is 138 companies. The data were analyzed using panel dataregression with the help of the E-views analysis tool. Based on the results ofdata analysis that has been carried out, it was found that Company Age hada negative and significant effect on the timeliness of submitting financialstatements. This shows that the older the age of the company, the timelinessof publication of the company's financial statements will be lower.Meanwhile, profitability estimated by ROA and Debt estimated by DER haveno significant effect on the timeliness of submitting financial reports tomanufacturing companies on the Indonesia Stock Exchange